Effective therapy with Bismuth-212 labeled macroaggregated albumin in orthotopic mouse breast tumor models - Kauffman, Nathan; Singh, Satyendra Kumar; Morrison, James; Zinn, Kurt R. (Frontiers in Chemistry, 2023)
Intravascularly administered radiation therapy using beta (β-)-emitting radioisotopes has relied on either intravenously injected radiolabeled peptides that target cancer or radiolabeled microspheres that are trapped in the tumor following intra-arterial delivery. More recently, targeted intravenous radiopeptide therapies have explored the use of alpha (α)-particle emitting radioisotopes, but microspheres radiolabeled with α-particle emitters have not yet been studied. Here, FDA-approved macroaggregated albumin (MAA) particles were radiolabeled with Bismuth-212 (Bi-212-MAA) and evaluated using clonogenic and survival assays in vitro and using immune-competent mouse models of breast cancer. The in vivo biodistribution of Bi-212-MAA was investigated in Balb/c and C57BL/6 mice with 4T1 and EO771 orthotopic breast tumors, respectively. The same orthotopic breast cancer models were used to evaluate the treatment efficacy of Bi-212-MAA. Our results showed that MAA can be stably radiolabeled with Bi-212 and that Bi-212-MAA can deliver significant radiation therapy to reduce the growth and clonogenic potential of 4T1 and EO771 cells in vitro. Additionally, Bi-212-MAA treatment upregulated H2AX and cleaved Caspase-3 expression in 4T1 cells. Biodistribution analyses showed 87-93% of the Bi-212-MAA remained in 4T1 and EO771 tumors 2 and 4 hours after injection. Following single-tumor treatments with Bi-212-MAA there was a significant reduction in the growth of both 4T1 and EO771 breast tumors over the 18-day monitoring period. Overall, these findings showed that Bi-212-MAA was stably radiolabeled and inhibited breast cancer growth. Bi-212-MAA is an exciting platform to study α-particle therapy and will be easily translatable to larger animal models and human clinical trials.